COMSOL simulation of microwave plasma polishing on different surfaces. (2021) - Yadav, Hari Narayan Singh; Kumar, Manjesh; Kumar, Abhinav; Das, Manas
Abstract: The characteristics of the surface and substrate have a significant role in the life and efficiency of the optical device. COMSOL® Multiphysics is a software program, which is applied to model the radio frequency (RF)-excited dielectric barrier for helium (processing gas) and oxygen (reactive gas). The software is flexible enough to accommodate multiple partial differential equations (PDEs) in a single domain model. This Multiphysics software is focused on finite element modelling program. The composition of the gas, the pressure, the configuration of the electrodes, and the excitation power of the RF are analyzed with regard to the formation of oxygen radicals and their consistency of allocation in the chamber. A computer program has been established to plan and optimize the microwave plasma physics utilized for the polishing of the surface of an optical specimen. The COMSOL® Multiphysics software is used for the simulation of microwave plasma coupled with an electromagnetic wave. COMSOL can easily simulate multiphysics problems. In the current study, a new method of producing Helium and Oxygen by microwave plasma is researched, evaluated, and simulated. The results show the distribution of density, temperature, and potential of electrons for two different specimens in the plasma chamber.